Heroes of the environment : True stories o0f people who are helping to protect our planet - Rohmer, Harriet (Scholastic, 2009)
In every story, you're right alongside the heroes as they take on the problems, overcome obstacles, and find succes. These twelve heroes represent just a few of the manu people who are working today to protect the earth and all its residents. Their stories will inspire you, and you'll learn how you can support, join - and even lead - efforts to heal our environment and keep it clean and healthy for generations to come.